2023
DOI: 10.1186/s11658-023-00447-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of noncoding RNAs in metabolic reprogramming of cancer cells

Amir Safi,
Mohammadreza Saberiyan,
Mohammad-Javad Sanaei
et al.

Abstract: Metabolic reprogramming is a well-known feature of cancer that allows malignant cells to alter metabolic reactions and nutrient uptake, thereby promoting tumor growth and spread. It has been discovered that noncoding RNAs (ncRNAs), including microRNA (miRNA), long noncoding RNA (lncRNA), and circular RNA (circRNA), have a role in a variety of biological functions, control physiologic and developmental processes, and even influence disease. They have been recognized in numerous cancer types as tumor suppressors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 202 publications
0
7
0
Order By: Relevance
“…These findings have significant consequences in relation to the development of therapies for metabolic disorders, such as cancer. For instance, investigators demonstrated that cytosolic lncRNAs and miRNAs are essential for controlling the expression of glucose transporters GLUT1-3 as well as glycolytic enzymes via HK2, which results in dysregulated glucose uptake in response to insulin and limits the conversion of glucose to glucose 6-phosphate thereby reducing the overall metabolic activity of mammalian cells [46,47]. Xu et al also found that lncMMPA alters the levels of ALDH1A3, affecting the rate of aerobic glycolysis in HCC, yet promotes M2 macrophage polarization [47].…”
Section: Ncrna Regulatory Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have significant consequences in relation to the development of therapies for metabolic disorders, such as cancer. For instance, investigators demonstrated that cytosolic lncRNAs and miRNAs are essential for controlling the expression of glucose transporters GLUT1-3 as well as glycolytic enzymes via HK2, which results in dysregulated glucose uptake in response to insulin and limits the conversion of glucose to glucose 6-phosphate thereby reducing the overall metabolic activity of mammalian cells [46,47]. Xu et al also found that lncMMPA alters the levels of ALDH1A3, affecting the rate of aerobic glycolysis in HCC, yet promotes M2 macrophage polarization [47].…”
Section: Ncrna Regulatory Potentialmentioning
confidence: 99%
“…For instance, investigators demonstrated that cytosolic lncRNAs and miRNAs are essential for controlling the expression of glucose transporters GLUT1-3 as well as glycolytic enzymes via HK2, which results in dysregulated glucose uptake in response to insulin and limits the conversion of glucose to glucose 6-phosphate thereby reducing the overall metabolic activity of mammalian cells [46,47]. Xu et al also found that lncMMPA alters the levels of ALDH1A3, affecting the rate of aerobic glycolysis in HCC, yet promotes M2 macrophage polarization [47]. Some of these metabolically linked-ncRNAs are also functionally active in the nucleus, and interact with DNA regulatory machinery to control cellular proliferation in response to glucose stimulation [48,49].…”
Section: Ncrna Regulatory Potentialmentioning
confidence: 99%
“…With its structure composed of the four canonical ribonucleotides—adenine (A), cytosine (C), guanine (G), and uracil (U)—and further complexity enriched with over 170 posttranscriptional chemical modifications observed across all life forms [ 5 ], RNA plays a crucial role in shaping cellular identity and directing a vast array of biological processes. Consequently, this brings to the fore the importance of comprehending RNA modifications, as they have far-reaching implications in both health and disease [ 6 9 ]. For instance, complementing our understanding of RNA modifications in host–pathogen interactions, we previously presented a pioneering study on spleen mRNA m 6 A methylation in response to malaria parasite infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are RNA molecules that are longer than 200 nucleotides and lack the ability to encode proteins [ 15 , 16 ]. Because of their unique involvement in cancer, lncRNAs have gained considerable attention [ 17 ].…”
Section: Introductionmentioning
confidence: 99%